2016
DOI: 10.4314/njt.v36i1.32
|View full text |Cite
|
Sign up to set email alerts
|

The Prospects, Impacts, and Research Challenges of Enhanced Cellulosic Ethanol Production: A Review

Abstract: The benefits and impacts of enhanced cellulosic ethanol (CE) production, the major features of existing production processes, and some current research challenges of major pretreatment processes are presented. The prospects of enhanced CE production, especially in developing economies like Nigeria are highlighted. We conclude that in order to reap the promising prospects and conquer the challenges and negative impacts of enhanced CE production, current researches for production of cellulosic ethanol must be fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Bioenergy from perennial plants, including forest biomass by planting suitable mixed tree species, offers a 'win-win' solution for restoration of degraded land and GHG emissions (IEA 2010). In addition to providing woody biomass for bioenergy production (Ezeoha et al 2017), mixed-species tree plantations -aka agroforestry -prevent soil erosion and siltation of waterways, create cooler microclimates, enhance biodiversity by providing suitable habitats for flora and fauna, including pollinators and natural predators (helping to spread risk of loss from pests and diseases) Further, the additional vegetation recuperates the soil and plant life through nutrient cycling and bolstering soil organic carbon, with above-and belowground biomass sequester atmospheric carbon, thereby providing emission reductions (Harvey and Guariguata 2020;ICRAF 2022).…”
Section: Restoration Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioenergy from perennial plants, including forest biomass by planting suitable mixed tree species, offers a 'win-win' solution for restoration of degraded land and GHG emissions (IEA 2010). In addition to providing woody biomass for bioenergy production (Ezeoha et al 2017), mixed-species tree plantations -aka agroforestry -prevent soil erosion and siltation of waterways, create cooler microclimates, enhance biodiversity by providing suitable habitats for flora and fauna, including pollinators and natural predators (helping to spread risk of loss from pests and diseases) Further, the additional vegetation recuperates the soil and plant life through nutrient cycling and bolstering soil organic carbon, with above-and belowground biomass sequester atmospheric carbon, thereby providing emission reductions (Harvey and Guariguata 2020;ICRAF 2022).…”
Section: Restoration Targetsmentioning
confidence: 99%
“…Wood-based bioenergy has up to 90% less GHG emissions than fossil diesel whereas maizebased ethanol only reduces emissions 10-20% (Montenegro 2006). When the life cycle is considered, grain-based ethanol produces net emissions attributed to the release of nitrous oxide (N2O) during ethanol production (Ezeoha et al 2017).…”
Section: Significant Reductions In Ghg Emissionsmentioning
confidence: 99%
“…Over the years, technology has geared towards developing new ways to transform waste into wealth. Whereas harnessing this biowaste in the production of bioethanol has numerous advantages [5,6], Hoang and Nghiem [7] reported that there is very little global commercial production of ethanol from cellulose.…”
Section: Introductionmentioning
confidence: 99%